1993 18th Conference on Local Computer Networks
DOI: 10.1109/lcn.1993.591268
|View full text |Cite
|
Sign up to set email alerts
|

Performance of high-speed networks for multimedia applications

Abstract: In a multimedia application, text, graphics, high quality sounds and video images are transmitted and processed. To have multimedia applications running on top of a network, the underlying network must ensure that all the messages will meet their deadlines. Messages missing their deadlines will result in a poorer quality of sound and video. In such a network, on-time delivery of messages is essential. This paper studies the real-time performance of several existing local-area network medium-access protocols un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…No asynchronous message is sent, but the station is allowed to send synchronous messages for a maximum time of H. After the transmission, the token will be released to the next station. [NG91,NG93A,NG93B,NG93C] In this paper, we set the two parameters TTRT and H j for each video stream S j where j = 1, 2, …, m, according to the normalized proportional allocation scheme proposed by Wei Zhao et al [AGR94,CHE92,MAL93,ZHA94]. Their work claimed that with the normalized-proportional allocation scheme for the timed token MAC protocol, one can achieve the highest worst-case achievable utilization of 33%.…”
Section: The Timed Token Mac Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…No asynchronous message is sent, but the station is allowed to send synchronous messages for a maximum time of H. After the transmission, the token will be released to the next station. [NG91,NG93A,NG93B,NG93C] In this paper, we set the two parameters TTRT and H j for each video stream S j where j = 1, 2, …, m, according to the normalized proportional allocation scheme proposed by Wei Zhao et al [AGR94,CHE92,MAL93,ZHA94]. Their work claimed that with the normalized-proportional allocation scheme for the timed token MAC protocol, one can achieve the highest worst-case achievable utilization of 33%.…”
Section: The Timed Token Mac Protocolmentioning
confidence: 99%
“…Furthermore, some of our previous studies [NG91,NG93A,NG93B,NG93C] have shown that the timed token MAC protocol is suitable for real-time communication and multimedia application within a local area network (LAN). The main idea behind the timed token MAC protocol is to control the sharing of network bandwidth among the stations for transmitting synchronous messages.…”
Section: Introductionmentioning
confidence: 99%
“…No asynchronous message is sent, but the station is allowed to send synchronous messages for a maximum time of H. After the transmission, the token will be released to the next station. [NG91,NG93A,NG93B,NG93Cl We set the two parameters TTRT and Hi for each station i according to the "normalized proportional allocation scheme" proposed by Wei Zhao [AGR92, CHE92, MAL93, ZHA941. The papers claimed that with the "normalized-proportional allocation scheme" for the FDDI network, one can achieve the highest worst-case achievable utilization of 33%.…”
Section: Network Parametersmentioning
confidence: 99%